The Crimean Khanate and the Ottoman Empire: The historiography of relations in the modern Russian science - D.A. Mustafina; I.A. Mustakimov (Ученые записки Казанского университета: Серия Гуманитарные науки)
This paper is devoted to the discussions held by Russian researchers about the relations of the Crimean Khanate with the Ottoman Empire in the second half of the 16th century. Military, political, and diplomatic contacts between these regions are of interest due to the absence of specialized works on this problem. Based on the available data, the conclusion has been made that the international relations in Eastern Europe during the studied period had a complex nature, which was mainly due to the development of the bases of the European political system. A great interest in the degree of independence of the Crimean policy towards the Ottoman Empire in Russian historiography is also worth mentioning. Obviously, the understanding of the problem depends on the selective approach which relies heavily on the character of the source base and on the limitations of the study by the specific territorial and political systems. Therefore, we can claim that Crimean-Ottoman affairs should be considered as an element of the most interwoven international relations in the second half of the 16th century. It is also very important to use not only well-known source material during investigation, but also documentary evidence from the archives.